Hemisection of a severely decayed mandibular molar: Case report - Cendranata Wibawa Ongkowijoyo; Latief Mooduto; Deavita Dinari; Riski Setyo Avianti (Universitas Airlangga, 2020)
Introduction: Dental implants gained popularity as the treatment to replace grossly decayed teeth. However, with the increasing evidence and the difficulty to manage complications associated with dental implants, clinicians are pushed to opt for a more conservative approach. Case report: A male patient with a chief complaint of frequent food impaction in a severely decayed mandibular molar wished to retain his tooth. Upon thorough examination, the carious lesion extended to furcal area that rendered the distal root unsalvageable. However the mesial root can be retained; thus, hemisection was proposed. Management: Root canal treatment was carried out in the mesial canals. Then, the tooth was split mesio-distally.The distal root was extracted, and the mesial root was retained. Subsequently, the tooth was restored with PFM crown.Conclusion: Hemisection with subsequent prosthetic rehabilitation can be a viable alternative to retain severely decayed mandibular molar.